Experimental Insights into Friction Losses of Post-Tensioned Precast Full-Scale Girders - Serry, Mostafa (AUC Knowledge Fountain, 2024)
The use of post-tensioning in construction has revolutionized the construction industry and made way for several construction and structural applications that were unattainable before. One of the most important topics that are synonymous with the use of post-tensioning is the matter of accurately calculating the short-term and long-term losses that arise in pre-stress. One of the prominent types of losses is the friction losses that occur during the jacking of the concrete elements due to its impact on structural integrity and longevity. The thesis examines this critical aspect of friction losses in post-tensioned concrete structures. The study focuses on full-scale, 30-meter precast girders, employing an experimental setup that involves the use of strain gauges embedded along the tendons within the concrete girders to measure and document the stress and strain behaviors during the jacking process. This analysis is motivated by the transformative effect of post-tensioning in the construction industry, which has enabled several new structural applications and spurred extensive research to refine and expand the understanding of post-tensioned systems. The research aims to bridge the gap between theoretical predictions and actual field results, providing a more accurate calculation of short-term losses due to pre-stress in such systems. Through this on-site investigation, the thesis provides empirical evidence highlighting that the friction losses occurring during the tensioning process are more pronounced and develop more rapidly than conventional models and standards predict. The findings from the experimental work and, eventually, the statistical processing of these obtained findings indicate that the friction losses measured were slightly greater than those forecasted by existing predictions, with a faster development of losses across the tendon's profile at varying levels of stress. These discrepancies underline the need for revisions in current engineering codes of practice and standards. The thesis thoroughly compares the experimental data with theoretical values from established literature and standards. Additionally, the research conducts regression analysis on the perceived dataset in order to propose an alternative prediction model for the matter of prestress losses, ultimately offering crucial insights and recommendations for improving the predictive accuracy and reliability of construction engineering calculations concerning post-tensioned concrete girders. Overall, the thesis not only advances the theoretical framework for understanding friction losses in post-tensioned structures but also contributes practical insights that can lead to more robust and reliable construction practices. This work underscores the importance of on-site validation of theoretical models and stresses the need for continuous adjustment of engineering codes to reflect real-world conditions more accurately.